Orientação profissional : impasses na escolha na graduação - Cruz, Edileuza Aparecida Silva (2020)
The choice of an undergraduate course is a crucial moment in the lives of subjects whose insertion in the university space, in addition to enabling the acquisition of specific knowledge in professional fields and preparing students to enter the world of work, has consequences in several aspects in the construction of an adult identity. Most individuals begin to question and be asked about their professional choice in adolescence, a period of physical, emotional and social changes that may be accompanied by doubts, insecurities and, for some young people, capable of generating intense psychological suffering. In the literature within the field of Psychology, which has focused on professional guidance, variables such as family identifications, affective repairs, social validation of the profession, identity construction processes can be present when the subject experiences his process of defining an undergraduate course. The objective of this study is to undertake an investigation of the subjective processes involved in the professional choice through the assistance in professional guidance by the clinical modality. Up to eight individual consultations were offered to students who sought the Applied Psychology Service at the Federal University of Mato Grosso, with impasses regarding the degree they chose. Most students report insecurities with the choice they made, a sense of loneliness and feel a lack of family and academic support for the anxieties experienced during graduation. The assistance helped to understand the students' internal conflicts and the personal meaning of the choice for the construction of occupational identity.